Dioctophyme renale Encapsulated in the Abdominal Cavity of a Dog - Borges Iepsen, Luã; Caye, Pâmela; Franco Bastos, Rodrigo; Borelli Grecco , Fabiane; Ladeira Sanzo, Gabriela; Moraes de Borba, Alana; Cristina da Silva Rappeti, Josaine (Acta Scientiae Veterinariae, 2024)
Background: Dioctophymosis is a zoonosis caused by the nematode Dioctophyma renale that affects terrestrial carnivores. Normally, the adult form of the worm develops in the kidney of these animals, but ectopic cases may occur. In addition, the disease has a challenging asymptomatic or nonspecific character, and thus, it is important to make an assertive and early definitive diagnosis through ultrasonography. The disease is primarily treated via surgical techniques. Therefore, this study reports a rare case of dioctophymiasis in a dog with an adult D. renale worm encapsulated in the abdominal cavity. Case: An adult male dog (19 kg) showing a penile lesion compatible with a transmissible venereal tumor and without other clinical symptoms was referred to the Veterinarian Clinics Hospital of the Federal University of Pelotas (UFPel), Brazil. The ultrasonography images revealed intra-abdominal changes that were suggestive of parasitosis by D. renale, presenting cylindrical structures with regular hyperechogenic edges and anechogenic internal content. The patient was referred for an exploratory laparotomy. Following an 8-h fasting period without solid food, preanesthetic medication, including methadone (0.3 mg/kg) and acepromazine (0.03 mg/kg), was intramuscularly administered. For anesthetic induction, propofol (2-5 mg/kg) was intravenously administered until it was possible to perform orotracheal intubation. For anesthetic maintenance, isoflurane (1.5 V%) diluted in 100% oxygen (50 mL/kg/min) was used in a semiclosed anesthetic circuit. The surgical approach involved a preretroumbilical incision in the median abdominal region. Upon accessing the abdominal cavity, a mass in the mesogastric region that was soft, irregular, yellowish, and measuring 10.5 × 5.5 × 3.8 cm was observed, and it was apparently adhered to the falciform ligament. A cold dissection of the structure was performed, followed by the ligation of small vessels with a 3-0 nylon thread, complete excision, and an abdominal suture in 3 layers. When the structure was dissected, a live and completely viable D. renale specimen was found, surrounded by seropurulent fluid, inside a cystic cavity covered with omentum. The excised capsular structure was sent for histopathological analysis, resulting in a conclusive diagnosis of granulation tissue. Discussion: When considering the dioctophymiasis cycle and the predominance of diagnosis of intrarenal parasites, the analysis of eggs in the urine is regarded as one of the primary screening methods. However, upon analyzing the patient’s urine immediately after admission to the hospital, no D. renale eggs were found in the sample. Definitive diagnosis was only possible using ultrasonography. The evidence of a viable worm inside a conjunctival capsule in the abdominal cavity indicates an erratic D. renale migration cycle. Furthermore, it was also confirmed that the parasite does not require kidney tissue for survival and can live in other parts of the body, thereby demonstrating the variety of clinical aspects in dioctophymiasis. This case indicates the possibility of unknown factors influencing the disease presentation, in agreement with similar cases reported in the literature. In the present case, the correct diagnostic approach made a definitive treatment possible. The surgical and anesthetic procedures occurred without complications and resulted in a satisfactory outcome, emphasizing the importance of understanding the complex clinical, surgical, and epidemiological aspects of dioctophymiasis. Keywords: dioctophymosis, ultrasonography, surgery, laparotomy, histopathology. Título: Dioctophyme renale encapsulado na cavidade abdominal de um cão Descritores: dioctofimatose, ultrassonografia, cirurgia, laparotomia, histopatologia.